PENGARUH LITERASI TIK TERHADAP TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) GURU : PENGARUH LITERASI TIK TERHADAP TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) GURU - Yessiana Dwi Maulidini (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
The development of the 21st century is characterized by the use of Technology, Information and Communication (ICT) in all aspects of life. Teachers in 21st century learning are expected to master technological knowledge, pedagogy, and content in conveying learning. Based on the facts, there are still many teachers who are lagging behind in the use of technology for the delivery of learning, the low pedagogical competence of teachers and the lack of understanding in delivering learning content. Those are some issues in the education field nowadays. Literacy toward teacher’s TPACK at Amaliah Elementary School Bogor. This research is a quantitative research by using functional correlation research design. The sample in this study amounted to 31 teacher’s. The research instrument used was a questionnaire with a Likert scale. Data were analyzed using regression equation analysis techniques, coefficient of determination, and significance tests to see significant effects. The results showed that there was a significant influence of ICT literacy on teacher’s TPACK. The results of this study concluded that the ICT literacy variable with teacher’s TPACK has a significant influence of 14.21% which means that both of these variables are classified as quite significant.